Environmentally Compatible Access to α‐Trifluoromethylseleno‐Enones. Issue 11 (2nd November 2020) - Grollier, Kevin; Taponard, Alexis; Ghiazza, Clément; Magnier, Emmanuel; Billard, Thierry
Abstract: α‐Trifluoromethylselenolated enones constitute valuable building‐blocks for further synthesis of innovative fluorinated compounds. Herein, we described an easy access to such compounds in green conditions through a Morita‐Baylis‐Hillman like reaction. These conditions have also been extended to higher fluorinated homologs. Abstract :